Effect of Job Burnout on employee level performance in Zhianawa Cancer Centre -Sulaimania City - كمال رشيد, نيان (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The aim of the research is to examine the effect of job burnout on employees Performance at the (Zhianawa Cancer Centre). After reviewing previous studies on the variables, Theoretical concepts were written and research questions were designed to collect data and distributed to the respondents of (61) employees at the centre, and (55) were analyzed:and verified its validity and reliability, the study followed the descriptive and analytical approach, several statistical methods were used to analyze the data and answer the hypothesis. The research reached many conclusions in light of results of the research. The results showed the existence of correlation and statistically significant effect between the job burnout and job performance of workers, a number of recommendations were presented including the need for the attention on the subject of job burnout because of negative effects on the employees health and decreasing their performance.